Chapter Determinants of the transition to upper secondary school: differences between immigrants and Italians - Frederic, Patrizio (Proceedings e report, 2021)
The determinants of the transition from lower secondary to upper secondary school of Italian and immigrant teenagers (16-19 age range) were identified joining the European Union Statistics on Income and Living Conditions (EU-SILC) and the Italian Survey on Income and Living Conditions of Families with Immigrants in Italy (IM-SILC) for 2009. A set of individual, family, and contextual characteristics was selected through the Lasso method and a Bayesian approach to explain the choice of upper secondary schooling (yes/no). The transition from the low secondary to upper secondary school showed a complex pattern involving many variables: compared to men, women did not prove to have any differences, many components of income entered the model in a parabolic form, education level and income of parents proved to be very important, as was their occupation. The contextual factors revealed their importance: the latter included the degree of urbanisation, the South macro-region, household tenure status, the amount of optional technological equipment, and so on. Differences between Italians and immigrants disappeared when family background and parental characteristics were taken into account.